Formulation and evaluation of colon targeted dosage form of prednisolone tablet using sterculia gum - Raghuvanshi, Neha Singh; Goswami, Laxmi; Kothiyal, Preeti (Journal of Applied Pharmaceutical Research, 2014)
Matrix tablets of Prednisolone were prepared by wet granulation method using various proportions of Sterculia gum with Carbopol 934P and Sterculia gum with Ethyl cellulose at 1:1, 1: .5 and 1:2 ratio. Coating was carried out by using 1:1 ratio of Eudragit L100 and Eudragit S100. All the preparation were evaluated for Pre compressional properties, Post compressional properties and in-vitro Dissolution study in different pH buffer of 0.1N HCL ,pH 7.4 , pH 6.8 in order to mimic GIT condition. Formulation shows good results with good percentage yield.